Comparison of Profile Attractiveness between Class III Orthodontic Camouflage and Predictive Tracing of Orthognathic Surgery - Mohamad Nagi Bou Wadi; Karina Maria Salvatore Freitas; Daniel Salvatore Freitas; Rodrigo Hermont Cançado; Renata Cristina Gobbi de Oliveira; Ricardo Cesar Gobbi de Oliveira; Guilherme Janson; Fabricio Pinelli Valarelli (International Journal of Dentistry)
Objective. The aim of this study was to compare the profile attractiveness between orthodontic camouflage of the Class III malocclusion and the predictive tracing simulating orthognathic surgery evaluated by dentists and laypeople. Settings and sample population. The sample consisted of 21 patients (9 male; 12 female) with Class III malocclusion treated with orthodontic camouflage and Class III intermaxillary elastics. Material and Methods. The mean initial age of the patients was 24.38 years (SD 3.32), and the mean ANB angle was −1.91° (SD 0.83°). Patients presented skeletal Class III and normal growth patterns. Initial and final lateral cephalograms of each patient were used. The initial cephalogram was used to perform the treatment simulation of orthognathic surgery, and its silhouette was compared to the silhouette obtained from the final cephalogram after Class III orthodontic camouflage. A subjective analysis of profile attractiveness was performed by 47 laypeople and 60 dentists, with scores from 1 (less attractive) to 10 (most attractive). Mann–Whitney tests were used to compare profile attractiveness between the orthodontic treatment and the predictive tracing groups and between dentists and laypeople. Results. The predictive tracing of orthognathic surgery showed to be statistically significantly more attractive (mean score 4.57, SD 2.47) than that of the Class III camouflage orthodontic treatment (mean score 4.22, SD 2.40), with a mean numerical but significant difference of 0.35 (SD 2.01) (P<0.001). Laypeople were more critical than dentists in evaluating profile attractiveness, but numerical difference between the groups was also small. Conclusion. The profile silhouette of predictive tracing simulating orthognathic surgery showed to be more attractive than that of Class III camouflage orthodontic treatment; however, differences were small but statistically significant. Laypeople showed to be more critical than dentists.